Exploring culturally-preferred communication approaches for increased uptake of voluntary medical male circumcision (VMMC) services in rural Malawi - Kent Yelemia G. Mphepo; Adamson Sinjani Muula; Joel Suzi; Felix Phuka; Joseph Mfutso-Bengo (BMC, 2023)
Abstract Background In 2007 WHO and UNAIDS recommended communication interventions as a key strategy for creating demand for Voluntary Medical Male Circumcision (VMMC) in Southern Africa. In Malawi, VMMC communication interventions, implemented by health communication agencies, have effectively raised awareness of services. However, high awareness of VMMC has not resulted in increased uptake. Consequently, Malawi has achieved the lowest number of circumcisions in Southern Africa. Methods These researchers carried out a study among the traditionally circumcising Yaos of Mangochi in Southern Region and the non-circumcising Chewas in Central Region. Data were collected using FGDs, KIIs, IDIs, Life Histories and Participatory Rural Appraisal methods. Data were analyzed thematically. Results This study demonstrates two lessons. First, Laswell's Theory, which has traditionally been used in politics, is relevant to the health sector where the message delivery continuum also needs to be clear on source, message, audience, channel and intended effects. Secondly, according to informants, allowing communities to give feedback to the VMMC messages delivered by health promoters is fundamental. Therefore, failure by Laswell Theory to emphasize on feedback compromises its efficacy. It weakens its ability to foster a common vision between the source and the audience which is prerequisite for behavioral change. Conclusion The study concluded that community engagement and interpersonal communication which provide room for real-time feedback in any communicative event are the most preferred communication interventions for VMMC services among Yaos and Chewas.